Developing Life Skills with Digital Comic Books to Improve Students' Critical Thinking Abilities in Science Subject - Karmila Bru Sebayang; Hasruddin Hasruddin; Sri Milfayetty (Randwick International of Education and Linguistics Science Journal, 2023)
This research aims to develop a life skills-based science material digital comic book teaching material product based on life skills that is feasible, practical and effective to use. This research uses development research (R&D) with a 4D model (Define, Design, Development, and Disseminate) with research subjects of 24 class IV students at SDN 068006 Medan. Data collection techniques use observation, tests, questionnaires and documentation. The results of the research produced feasibility with an average percentage of 91% in the "Very Feasible" category, the practicality test percentage was 79% in the "Practical" category. Next, test effectiveness through student pretest and posttest scores with an N-Gain of 0.51 for the "Effective" criterion. So, it can be concluded that digital comic book teaching materials based on life skills can be used in the learning process.